Pengembangan Instalasi Penerangan dan Instalasi Tenaga Listrik Mushalla Al-Barkah Lambung Bukit Kecamatan Pauh - Yudia Meka Seftiani; Aulia Oktavia; Riza Widia; Witri Onanda; Nofri Dodi; Firmansyah Firmansyah (Jurusan Teknik Elektro, Universitas Andalas, 2023)
Lambung Bukit Batu Busuk, Pauh, located in Padang City, West Sumatera established a prayer room which was named Mushalla Al-Barkah. This mushalla is used as a place of worship for muslims around Lambung Bukit Batu Busuk Padang. Some of the the worship activities carried out at the mushalla, include congregational prayer activities, Al-Qur’an education and other worship activities. These activities really need electricity in their implementation. The mushalla need loudspeakers to adzan, the mushalla needs lights for lighting at night. However, the incomplete installasyion of electrical installations in the mushalla has resulted in delays in worship activities in the mushalla for the community around Lambung Bukit Batu Busuk, Padang. Because of that the community implementation team carried out the development of lighting installastions and elekctric power installasions at Mushalla Al-Barkah. After this activitiy was complete at the mushalla, the mushalla’s electrical installation was perfect. This activity is useful for partners and can be used as a promotional agenda for the people Lambung Bukit, Pauh to get to know the Padang State Polytechnic.